Scaffolding on Student Construction Errors in Mathematics Problem Solving - Isnania, Isnania; Huda, Nizlel; Hariyanto, Hariyanto (Universitas Islam Negeri Raden Intan Lampung, 2021)
The Purpose of this study is to find out what forms of conceptual construction errors experienced by students in solving mathematical problems and the appropriate form of scaffolding for each concept construction error experienced. This type of research is descriptive qualitative research. In determining the subject of this study using purposive sampling technique. The research subjects were students of class XII, the subjects of this study were 6 people which were then reduced to 2 people representing medium and low abilities. The instruments used in this study were test questions and interview sheets. The data obtained were analyzed by the steps (1) Reducing the data. (2) presenting data and (3) drawing conclusions. The results of this study are that S1 experienced more “correct” pseudo construction errors and mis-logical construction with the scaffolding provided, namely level 2 (reviewing, explaining and restructuring) while S2 experienced four types of errors with the scaffolding provided, level 2 scaffolding. each individual will be different because it must be adjusted to the actual development zone of each.